Advancing Airfield Pavements 2001
DOI: 10.1061/40579(271)3
|View full text |Cite
|
Sign up to set email alerts
|

Slow-Rolling Response Tests on the Test Pavements at the National Airport Pavement Test Facility (NAPTF)

Abstract: Airport pavement thickness design procedures predict a significant amount of interaction between the loads from multiple-wheel and closely spaced multipletruck landing gear configurations. But the true degree of interaction is not known, and measurements from full-scale tests are required to determine how closely wheels and trucks can be spaced without significant load interaction. As a supplement to traffic tests run to failure at a later date, pavement response tests were performed to study the wheel load in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Tests were run at wheel loads of 106.8, 133.5, and 160.2 kN (24,000, 30,000, and 36,000 lbs) at each speed. Module 1-1 and Module 2-1 on Carriages 1 and 2, respectively, were used for testing (for carriage and load module details, refer to Hayhoe, 2001). Carriage offset was 3.81 m (12.71 feet) on either side of the pavement centerline.…”
Section: Special Tests On Asgsmentioning
confidence: 99%
“…Tests were run at wheel loads of 106.8, 133.5, and 160.2 kN (24,000, 30,000, and 36,000 lbs) at each speed. Module 1-1 and Module 2-1 on Carriages 1 and 2, respectively, were used for testing (for carriage and load module details, refer to Hayhoe, 2001). Carriage offset was 3.81 m (12.71 feet) on either side of the pavement centerline.…”
Section: Special Tests On Asgsmentioning
confidence: 99%
“…As-constructed cross-sectional views of these two test items considered in this study are shown in Figure 10. The gradation information, laboratory compaction properties and material characterisation test results for the sub-grade soils, P-209, and P-154 geomaterials are contained in the FAA's materials database (accessible for download at the FAA Airport Technology website: www.airporttech.tc.faa.gov) (Hayhoe and Garg 2001). During the first series of full-scale traffic tests, a sixwheel dual-tridem (B777) landing gear, with 1372 mm (54 inches) dual spacing and 1448 mm (57 inches) tandem spacing was loaded on the north wheel track (LANE 2) while the south side (LANE 5) was loaded with a four-wheel dual-tandem (B747) landing gear having 1118 mm (44 inches) dual spacing and 1473 mm (58 inches) tandem spacing.…”
Section: Acquisition Of Field Datamentioning
confidence: 99%
“…Located at the FAA William J. Hughes Technical Center, Atlantic City International Airport, New Jersey, the National Airport Pavement Test Facility (NAPTF) aims at generating full-scale pavement response and performance data for the development and verification of airport pavement design criteria. The NAPTF became operational on April 12, 1999 and consists of a 900 feet long by 60 feet wide test pavement area, embedded pavement instrumentation with dynamic data acquisition system, environmental instrumentation with static data acquisition system, and the NAPTF test vehicle for trafficking the test pavement with configurations of up to eighteen wheels with loads up to 75,000 pounds per wheel ( 1, 2 ).…”
mentioning
confidence: 99%